GESTIÓN DEL CLIMA ESCOLAR Y SU INCIDENCIA EN EL PROCESO DE ENSEÑANZA-APRENDIZAJE DE LOS ESTUDIANTES DE 5TO AÑO DE LA UNIDAD EDUCATIVA 'ADOLFO MARÍA ASTUDILLO' Y DE LA ESCUELA DE EDUCACIÓN BÁSICA 'AURORA ESTRADA Y AYALA DE RAMÍREZ PÉREZ' DE LA PARROQUIA CAMILO PONCE LUQUE, CANTÓN BABAHOYO, PERIODO LECTIVO 2024-2025. - CORREA DUARTE JESSICA MARIA (2024)
Adequate management of the school climate in educational institutions is essential in the construction of a school environment that is conducive to the teaching-learning process, this includes aspects such as interpersonal relationships between educational actors, the involvement of representatives, the management of conflicts and problem solving, analyzing how these aspects affect the management of the school climate will generate a sense of commitment in the way this situation is addressed, which is why this project aims to determine the incidence of school climate in the teaching-learning process of 5th year students of the "Adolfo María Astudillo" Educational Unit and the "Aurora estrada y Ayala de Ramírez Pérez" Educational Unit. The problem focuses on the inadequate management of the school climate, which is reflected in problems of indiscipline, which stem from poor interpersonal relationships between actors in the educational community, affecting the school climate and therefore the teaching-learning process. A quantitative research approach will be used, this being a descriptive research, the technique that will be used will be the survey and the instrument will be the questionnaire. The results revealed that there are specific areas for improvement such as interpersonal relationships, preventive actions and approaches to conflict resolution. It is concluded that a healthy school climate promotes mutual respect, collaboration and a sense of belonging, essential elements for a comprehensive teaching-learning process.